Preferences and willingness for starting daily, on-demand, and long-acting injectable HIV pre-exposure prophylaxis among transfeminine persons in the US, 2022–2023 - Duygu Islek; Travis Sanchez; Stefan Baral; Carolyn Brown; Joanna A. Caldwell; Jennifer L. Glick; Danielle Friedman Nestadt; Jeb Jones; Iaah L. Lucas; Supriya Sarkar; Annemiek de Ruiter; Patrick S Sullivan; et al. (PLoS ONE, 2025)
Background There remains limited information concerning US transfeminine persons preferences across varying PrEP options. We examined PrEP option willingness, preferences, and associated factors among a US nationwide sample of transfeminine persons. Methods Sexually active transfeminine persons age 15 + were recruited online between June 2022-October 2023 through social media advertisements. Transfeminine persons not diagnosed with HIV were asked about willingness to initiate, and ranked preference, of three PrEP options– daily oral (DO), on-demand, and long-acting injectable (LA-PrEP). Log-binomial models were used to examine PrEP modality willingness and associated sociodemographic and behavioral characteristics. Results Among 2657 transfeminine persons not currently using PrEP, 51% reported willingness to start at least one PrEP option. The highest willingness was reported for on-demand PrEP (42.6%), followed by DO (38.1%) and LA PrEP (27.1%). LA PrEP was ranked the most preferred PrEP option among transfeminine persons who reported willingness to start multiple PrEP options (43%, 277/651). Willingness to start on-demand PrEP was higher among participants who were 15-24 years, resided in the South, did not have health insurance, had more than one sex partners and reported prior awareness of on-demand PrEP. Willingness to use DO and LA PrEP was higher among those who had both private and public insurance, reported condomless anal sex, had more than one sex partners and had used non-injection illicit drugs. Additional factors for DO and LA PrEP willingness was residing in the South and prior awareness of LA PrEP, respectively. Conclusions Among transfeminine persons, the highest willingness was reported for on-demand PrEP; and LA PrEP was ranked the most preferred option among those who reported willingness to try multiple options. Offering a variety of PrEP options, informed by an understanding of individual preferences and socio-demographic and behavioral differences, can increase overall PrEP uptake and help meet diverse needs of the transfeminine community.